Uma proposta de aplicação do protocolo “Cells-In-Frames” para a interconexão de redes ATM e IEEE 802.3/Ethernet - Boaventura, Taciana Tiradentes (1998)
Searching for Solutions to existing legacy LANs and ATM networks interoperability problem has been the purpose of many current studies. Due to the great number and complexity of applications being used in non-ATM networks, in most cases, it is not feasible to carry all of them to ATM networks. For that reason, several alternatives have been defined to enable the connection between legacy LANs and ATM technology. The greatest challenge has been, therefore, to assure the continuation of Services and interfaces that already exist nowadays, though aiming at the total and effective integration of all kinds of applications and communication Services. The “Cells-In-Frames” protocol makes this interoperability feasible by means of carrying ATM cells as payload in the frames of legacy LANs; thus providing support for ATM Services in them. This way it becomes possible for the legacy LAN to offer advantages that would only be found in ATM networks, such as QoS support. Thus upper layer protocols are allowed to operate exactly as if there were a single ATM network, hence taking advantage of the characteristics of ATM best performance. In this work, a study of the behavior and performance of the “Cells-In-Frames” mechanism applied to a system aimed at the interconnection of ATM networks and IEEE 802.3/Ethernet has been carried out. This study was based on modelling and simulation.